Analisis Kemampuan Literasi Digital Mahasiswa Jurusan Pendidikan Geografi Fakultas Ilmu Sosial Universitas Negeri Medan - Mendrofa, Verry Sisca; Berutu, Nurmala (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2024)
This study aims to analyze the Digital Literacy Skills Students of Geography Education Department, Faculty of Social Sciences, Universitas Negeri Medan. The data collection techniques used were tests and questionnaires as well as direct observation of respondents' social media accounts, then analyzed using descriptive statistical techniques. The results showed that: Overall, the digital literacy skills of Geography Education Department students are classified as good with an average score (70.58) and percentage score (63.58%). When viewed according to its aspects, the knowledge aspect is classified as good with an average score (8.39) and percentage score (64.58%), the attitude aspect is classified as very good with an average score (42.83) and percentage score (85.67%), but the skill aspect is less with an average score (19.35) and percentage score (40.31%). The digital literacy ability of men with an average score (70.71) and percentage score (63.71%) was higher but not significantly different from women who had an average score (70.51) and percentage score (63.52%). Most students of Geography Education Department are not very active in using social media (84.06%) and their uploads are more personal content (30.57%) than work content (4.26%).